Endotoxin-Induced Maturation of MyD88-Deficient Dendritic Cells - Tsuneyasu Kaisho; Osamu Takeuchi; Taro Kawai; Katsuaki Hoshino; Shizuo Akira (2001)
Abstract LPS, a major component of the cell wall of Gram-negative bacteria, can induce a variety of biological responses including cytokine production from macrophages, B cell proliferation, and endotoxin shock. All of them were completely abolished in MyD88-deficient mice, indicating the essential role of MyD88 in LPS signaling. However, MyD88-deficient cells still show activation of NF-κB and mitogen-activated protein kinase cascades, although the biological significance of this activation is not clear. In this study, we have examined the effects of LPS on dendritic cells (DCs) from wild-type and several mutant mice. LPS-induced cytokine production from DCs was dependent on MyD88. However, LPS could induce functional maturation of MyD88-deficient DCs, including up-regulation of costimulatory molecules and enhancement of APC activity. MyD88-deficient DCs could not maturate in response to bacterial DNA, the ligand for Toll-like receptor (TLR)9, indicating that MyD88 is differentially required for TLR family signaling. MyD88-dependent and -independent pathways originate at the intracytoplasmic region of TLR4, because both cytokine induction and functional maturation were abolished in DCs from C3H/HeJ mice carrying the point mutation in the region. Finally, in vivo analysis revealed that MyD88-, but not TLR4-, deficient splenic CD11c+ DCs could up-regulate their costimulatory molecule expression in response to LPS. Collectively, the present study provides the first evidence that the MyD88-independent pathway downstrem of TLR4 can lead to functional DC maturation, which is critical for a link between innate and adaptive immunity.